Recomendação de calagem para o sistema soja/milho na região de transição Cerrado/Amazônia - Pinto, Adenilson Carlos (2021)
In areas consolidated under the no-tillage system, proper construction and maintenance to correct soil acidity is a strategy to increase agricultural production. This study considered the hypothesis that base saturation estimated by the most used methods cannot reach the same or close to the desired values and thus the increase in doses and the use of different sources of lime in a medium textured soil under consolidated SPD may improve the chemical attributes of the soil and increase the productivity of soybean and corn crops. The objective was to evaluate the increase in lime doses, based on two methods of liming calculation and the mixture between correctives, with or without incorporation in the 0 to 0.2 m layer, looking for the effects on improving the soil and the increase in productivity in the soybean/corn system for two consecutive years. Two limestones with different concentrations of Ca and Mg were used, one with 30.6% of CaO and 18.1% of MgO and the other with 47% CaO and 0.3% MgO, hereinafter called C1 and C2, respectively. To calculate the doses, the base saturation or V% method was used, and the method of increasing the Ca and Mg contents of the soil based on the Ca and Mg contents of the limestones. Liming was carried out on October 9, 2018, in a consolidated no-tillage area in the municipality of Querência-MT, establishing eight field treatments with four replications. The treatments were (T1): without liming; (T2): V% 75; (T3): 1.75*T2; (T4): 3.27*T2, all with C1 limestone on the surface; (T5): 60% Ca and 20% Mg in CTC, (T6): 75% Ca and 25% Mg in CTC, with a mixture of limestones C2 and C1; (T7): 3.6*T2, divided into two seasons, with limestone C2 at implantation and C1 at 8 months, and (T8): 3.6*T2, being ½ incorporated (C2) and ½ on surface (C1 ). The components of production and productivity of soybean and corn were evaluated and soil samples were collected after the corn harvest, in June 2019 and 2020. Liming carried out with incorporation obtained better results only in the first harvest, the increase in doses did not resulted in a significant productive increase for the period evaluated, the mixture between the correctives provided better contents of Ca and Mg in the soil and the ratio between them being above 3:1, the two methods underestimated the doses of lime in the desired correction.